Building Psychological Safety and Employee Voice to Mitigate Operational Failures in Distressed Organizations - Heddy Setiawan (Asian Journal of Management Analytics, 2026)
Distressed organizations face heightened operational failures due to uncertainty, resource pressure, and limited upward communication. This study aims to examine the relationship between psychological safety, employee voice, and operational failure mitigation in human resource management. A quantitative survey design was employed by collecting questionnaire data from 156 employees in organizations experiencing performance distress, and the data were analyzed using multiple linear regression. The findings show that psychological safety significantly strengthens employee voice, while employee voice contributes to the early identification and reduction of operational failures. Psychological safety also supports failure mitigation through open reporting and constructive feedback. This study contributes to human resource management theory by linking socio-psychological work climate with operational resilience and offers practical guidance for improving failure prevention in distressed organizations.